5 years of must reads from hbr 2021 edition (5 books) - Review, Harvard Business. (Harvard Business Review Press, 2020)
Five years' worth of management wisdom, all in one place. Get the latest, most significant thinking from the pages of Harvard Business Review in 5 Years of Must Reads: 2021 Edition. Every year, HBR editors examine the ideas, insights, and best practices from the past twelve months to select the definitive articles that have provoked the most conversation, the most inspiration, and the most change. From how you can lead with authenticity by moving past your comfort zone, to understanding how blockchain will affect your industry, to creating a workplace where gender equity can thrive, the articles in this five-book collection will help you manage your daily challenges and meet the changing competitive landscape head-on. Books in the HBR 10 Must Reads series offer essential reading selected from the pages of Harvard Business Review on topics critical to the success of every manager. Each book is packed with advice and inspiration from leading experts such as Clayton Christensen, Michael Porter, W. Chan Kim, Renee Mauborgne, Herminia Ibarra, Marcus Buckingham, Joan C. Williams, Roger Martin, Adam Grant, and Katrina Lake. Company examples range from Pepsico, DHL, and Deloitte to Alibaba, Adobe, and Stitch Fix. 5 Years of Must Reads: 2021 Edition brings the most current and important business conversations to your fingertips.